162k views
0 votes
Drag the correct steps into order to solve the equation 6x+6= -12 for x

User Oberlies
by
5.3k points

2 Answers

1 vote

Answer:

x = -3

Explanation:

Isolate the variable, x. Note the equal sign, what you do to one side, you do to the other. Do the opposite of PEMDAS.

First, subtract 6 from both sides:

6x + 6 (-6) = -12 (-6)

6x = -12 - 6

6x = -18

Isolate the variable, x. Divide 6 from both sides:

(6x)/6 = (-18)/6

x = (-18)/6

x = -3

x = -3 is your answer.

User Muecas
by
5.2k points
0 votes

Answer:

x = -3

Explanation:

Isolate the variable, x. Note the equal sign, what you do to one side, you do to the other. Do the opposite of PEMDAS.

First, subtract 6 from both sides:

6x + 6 (-6) = -12 (-6)

6x = -12 - 6

6x = -18

Isolate the variable, x. Divide 6 from both sides:

(6x)/6 = (-18)/6

x = (-18)/6

x = -3

x = -3 is your answer.

~

User John Humanyun
by
5.6k points